Nationalism and state control in Russia: A weakened social consensus - Marlène Laruelle (Revista CIDOB d'Afers Internacionals, 2011)
Nationalism in Russia is played out on several registers. It is the instrument by which the ruling elites succeed in effacing (at least superficially) their internal divisions and unifying the political spectrum under their banner. It can also be likened to a new form of state-proposed social contract, an attempt to remobilise society to its advantage by drawing on those elements of its cultural reservoirs that form a consensus around the theme of patriotism. Lastly, for the tiny proportion of the population committed to radical right-wing parties, it makes it possible to mobilise against the “other” at a time when massive social discontent is being expressed in xenophobic terms. Nationalism is therefore akin to an amalgam that reveals the multiplicity of current social and cultural experiences in contemporary Russia. Through nationalism, those who have lost out as a result of the reforms formulate their critique of the present and their nostalgia for the past, whereas the elites and the middle classes that have gained from these changes express their satisfaction and belief that Russia will win the game of globalisation.